A tomada de decisão estratégica em exploration ou exploitation e a folga de recursos organizacionais - Vicente, Simone César da Silva (2022)
Slacks of organizational resources, available, potential, or recoverable, are a challenge for the CEO (Chief Executive Officer). Both the available slack (cash flows, liquidity) and the potential slack (financing, loans) are more commonly used in strategies such as company acquisitions, and recoverable slack (excess equipment and people) is less observed for this type of strategy. The CEO’s decision to acquire companies with resource slack may be strategically directed into two options, acquisitions closer to the known (exploitation) or further away from the known (exploration). Evidently, environmental, organizational, and behavioral factors can influence the decision-making process. In this sense, the results are inconclusive and ambiguous as expected, whether more exploration or exploitation. Based on this finding, I sought to identify the effect of resource slack on the CEO’s decision making in acquisitions of companies in exploration or exploitation. Thus, I carried out three studies: literature review, bibliometric study, and an empirical study. In the literature review, I searched for the factors that relate the three types of organizational resource slack with exploration and exploitation. Subsequently, in the bibliometric, the main theoretical relationships between CEO decision-making and company acquisitions. Finally, an empirical study, with regression analysis, between available and potential resource slacks, exploration acquisitions and exploitation moderated by the CEO's term of office. The results showed us the importance of new research regarding behavioral aspects in the field of strategy. Traditional variables, organizational and environmental, are frequently used and are already consolidated in the literature, while behavioral variables may suggest good debates. Therefore, the results showed that organizational slack may reflect different effects on the company. First, as to how much slack the company has and how managers recognize it. The literature review showed us how the meaning of exploration (radical innovations) and exploration (incremental innovations) is still dubious. This is confirmed with more slack, more exploration and less slack will occur, more exploitation. The results of the second study identified several elements related to CEO and company acquisitions, involving financial resources, the CEO’s profile and his or her behavior were relevant for the decision to acquire another company. In I third study I found that the CEO’s term of office negatively moderates the relationship between potential slack and the degree of exploration-exploitation, concluding that the less time in the term, the more exploration and that the available slack contributes to the potential in this relationship. This thesis, with the three studies, provided some results, which both together and separately can contribute to the literature in several ways. The contribution, in essence, is to top-level theory, CEOs’ decision-making is critical to determining strategies triggering in companies' performance. Studying how they make decisions can suggest companies how to manage the time that the CEO can stay in charge and not impact the company's overall strategies. On the other hand, the decision regarding resource slack is still ambiguous and inconclusive in the literature, especially regarding ambidexterity- exploration and exploitation, which need to be analyzed in future research.